Community Composition and Diversity of Intestinal Microbiota in Captive and Reintroduced Przewalski’s Horse (Equus ferus przewalskii) - Li, Yimeng; Zhang, Ke; Liu, Yang; Li, Kai; Hu, Defu; Wronski, Torsten (Frontiers in Microbiology, 2019)
Large and complex intestinal microbiota communities in hosts have profound effects on digestion and metabolism. To better understand the community structure of intestinal microbiota in Przewalski’s horse (Equus ferus przewalskii) under different feeding regimes, we compared bacterial diversity and composition between captive and reintroduced Przewalski’s horses, using high-throughput 16S-rRNA gene sequencing for identification. Reintroduced Przewalski’s horses were sampled in two Chinese nature reserves, i.e. Dunhuang Xihu Nature Reserve (DXNR; n = 8) in Gansu Province and Kalamaili Nature Reserve (KNR; n = 12) in Xinjiang Province, and compared to a captive population at the Przewalski’s Horse Breeding Center in Xinjiang (PHBC; n = 11). The composition of intestinal microbiota in Przewalski’s horses was significantly different at the three study sites. Observed species was lowest in DXNR, but highest in KNR. Lowest Shannon diversity was observed in DXNR, while in KNR and PHBC had a moderately high diversity; Simpson diversity showed an opposite trend compared with the Shannon index. Linear Discriminant Analysis effect size was used to determine differentially distributed bacterial taxa at each study site. The most dominant phyla of intestinal microbiota were similar in all feeding regimes, including mainly Firmicutes, Bacteroidetes, Verrucomicrobia and Spirochaetes. Differing abundances of intestinal microbiota in Przewalski’s horses may be related to different food types at each study site, differences in diversity may be attributed to low quality food in DXNR. Results indicated that diet is one of the important factors that can influence the structure of intestinal microbiota communities in Przewalski’s horse. These findings combined with a detailed knowledge of the available and consumed food plant species could provide guidelines for the selection of potential future reintroduction sites.